2006
DOI: 10.1002/anie.200600329
|View full text |Cite
|
Sign up to set email alerts
|

A Priori Theoretical Prediction of Selectivity in Asymmetric Catalysis: Design of Chiral Catalysts by Using Quantum Molecular Interaction Fields

Abstract: Much effort has been devoted toward the development of asymmetric catalysts for the synthesis of chiral compounds in pure form.[1] Despite this body of work, the science of asymmetric catalysis remains far from exact, and the process of finding a new catalyst usually requires a large investment of manpower and funding. Therefore, a major goal is the development of more efficient methods for identifying highly selective asymmetric catalysts. In terms of computational methods, the calculation of ground state and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
53
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 36 publications
(17 reference statements)
0
53
0
Order By: Relevance
“…2 Additionally, β -amino alcohols, which are derivatives of α -amino cyclic ketones, are widely used as chiral ligands in asymmetric catalysis. 3 The past decade has witnessed the development of direct asymmetric α -amination of carbonyl compounds as a useful method for the preparation of chiral amine-containing structures. 4 Despite these advances, the majority of reported reactions rely on activated carbonyl compounds, such as 1,3-dicarbonyls, 2-oxindoles, α -cyanoacetates, and other reactive substrates.…”
mentioning
confidence: 99%
“…2 Additionally, β -amino alcohols, which are derivatives of α -amino cyclic ketones, are widely used as chiral ligands in asymmetric catalysis. 3 The past decade has witnessed the development of direct asymmetric α -amination of carbonyl compounds as a useful method for the preparation of chiral amine-containing structures. 4 Despite these advances, the majority of reported reactions rely on activated carbonyl compounds, such as 1,3-dicarbonyls, 2-oxindoles, α -cyanoacetates, and other reactive substrates.…”
mentioning
confidence: 99%
“…The replacement of the axial Ha with a larger phenyl substituent results in a further increase in enantioselectivity from 59% ee to 94% ee (ligand 10 vs 14b). 15 Likewise, another method for enhancing the diastereofacial selectivity of 11 is to substitute the axial hydrogen atom Hb in 11 with a bulky R 00 group, to give chiral catalyst 13. Indeed, experiments for the asymmetric addition of diethylzinc to benzaldehyde revealed that the chiral ligand 15 exhibits very high enantioselectivity (up to 98% ee).…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, computational screening methods strive to illustrate structural, dynamic, and binding information at an atomic level, making it necessary for the better understanding of sequence-structure-activity relationship and design principles for peptides mimetics. The QSAR is currently an important contributor to rational design of drugs, materials, catalysts, and proteins/peptides with desirable activities and functions [13][17]. The underlying hypothetical principle of QSAR models is to define mathematical relationships between a set of molecular descriptors and a given activity (chemical, physical, or biological activity) as an end point, to predict the activity of unknown ligands [18][29].…”
Section: Introductionmentioning
confidence: 99%